Perception of the elderly population on HIV/AIDS: na integrative review (Research, Society and Development, 2021)
AIDS is defined as a chronic infection resulting from the action of the HIV virus, which increases the vulnerability of the individual to numerous diseases of an opportunistic nature. Society labels the elderly population as asexual or not interested in sex, creating obstacles that can make coping difficult. The work aims to show the perception of the elderly population about HIV/AIDS, social aspects involved and the role of health professionals in this regard. This is an integrative review of the literature in medline, BDENF, LILACS and SciELO databases in which the PICO/PRISMA strategy was adopted using the descriptors: Aged, HIV, Knowledge. The elderly are increasingly living with HIV/AIDS, but are seen by others as non-sex practitioners, have an active sexual life and, there is preference for not using condoms, especially in male elderly. Condoms are seen only as contraceptives to the detriment of prevention. Women are more likely to get HIV infection due to age and culture issues. Elderly inhabitants of rural areas are even more vulnerable and have greater difficulties in care, compared to those living in urban areas. It is observed the need to perform actions more directed to the sexual health of the elderly, request for tests and supply of female and male condoms. It is urgently necessary to create policies on the need to plan, guide and implement actions with a view to the empowerment of the elderly in the face of hiv/AIDS prevention, intervention and diagnosis.